Hubungan Hukum Dalam Pelayanan Kesehatan - Widjaja, Gunawan; Mailinda, Nur (CV. Creative Tugu Pena, 2024)
In the world of health services, the relationship between law and medical practice is something that is difficult to control because it is related to good and transparent communication between all parties involved, including doctors, patients and legal parties. The research method used in this study is literature where theory is taken according to the research context. Research findings show that legal relationships in health services are an important aspect that regulates behavior and responsibilities between health service providers, patients and other related parties. The application of the law in the context of health care helps ensure safety, quality and protection of patient rights. Apart from that, in the context of health services there is also a contract between the health service provider and the patient, which regulates the rights and obligations of each party. This contract protects patients from malpractice, misuse of medical information, and ethical lapses. This research also makes a contribution to law and health where the relationship between law and health services ensures the protection of patient rights, maintains the quality of health services, and creates a framework for resolving conflicts and improving health policies Keywords: Law, Health Services, Law Medical Practice